RFID security authentication scheme based on Montgomery-form elliptic curve cryptography - Wumei ZHANG (Dianxin kexue)
For the issues that the existing RFID security authentication scheme based on elliptic curve cryptography （ECC）can not meet the requirements of mutual authentication,privacy protection and forward security,a RFID security authentication scheme based on Montgomery-form elliptic curve cryptography was proposed.This scheme uses the Montgomery elliptic curve to reduce the amount of computation,and to provide mutual authentication between the label and the server,and anonymity and forward security.The analysis showed that the scheme could resist replay attack,tag camouflage attack,server cheat attack,DoS attack,position tracking attack and clone attack.Compared with the existing schemes,the proposed scheme provides high security performance under low memory,computation and communication requirements,and it can meet the security requirements of the RFID system.